Interaction of Sex and Age on the Dissociative Effects of Ketamine Action in Young Healthy Participants - Derntl, B.; Hornung, J.; Sen, Z. D.; Colic, L.; Li, M.; Walter, M. (Frontiers in Neuroscience, 2019)
Ketamine is a drug that reduces depressive and elicits schizophrenia-like symptoms in humans. However, it is largely unexplored whether women and men differ with respect to ketamine-action and whether age contributes to drug-effects. In this study we assessed dissociative symptoms via the Clinician Administered Dissociative States Scale (CADSS) in a total of 69 healthy subjects aged between 18-30 years (early adulthood) after ketamine or placebo infusion. Dissociative symptoms were generally increased only in the ketamine group post-infusion. Specifically, within the ketamine group, men reported trendwise more amnestic symptoms than women. Furthermore, with rising age only men were less affected overall with respect to dissociative symptoms. This suggests a sex-specific protective effect of higher age which may be due to delayed brain maturation in men compared to women. We conclude that it is crucial to include sex and age in studies of drug effects in general and of ketamine-action in specific to tailor more efficient psychiatric drug-treatments.